Use of Propensity Score Matching to Compare Short Outcomes from Transoral and External Surgical Approaches in Patients with Deep-Lobe Parotid Pleomorphic Adenomas. - Yue Fan; Shuguang Li; Shuting Yu; Xiaoli Zhu; Xiaohua Shi; Wuyi Li; Zhiqiang Gao; Xingming Chen (Current Oncology, 2021)
To compare the outcomes of patients who had deep-lobe parotid gland pleomorphic adenomas (PAs) that extended into the parapharyngeal space after surgical treatment, using a transoral approach or an external approach. One hundred and twelve eligible patients, with deeplobe parotid gland PAs, were enrolled in this retrospective study. The surgical outcomes were compared for patients who received a transoral approach and an external approach, using 1:1 propensity score matching (PSM). The outcome measures were recurrence rate, facial nerve deficit, Frey's syndrome, and hospitalization time. The median follow-up time was 4.8 years. After PSM, the transoral approach and external approach groups had no statistically significant difference in recurrence (10.3% vs. 3.4%; p = 0.201). The transoral approach group had no facial nerve deficit, but 5 of 29 patients (17.2%) in the external approach group had transient facial nerve paralysis (p = 0.052). The external approach group had a longer hospitalization time than the transoral approach group (5 vs. 4 days, p = 0.0017). The use of a transoral surgical approach to treat patients with deep-lobe parotid gland PAs led to low recurrence, shorter hospitalization times, and good functional and cosmetic outcomes.